Resuscitation of trauma patients- an overview - Rabindran Chandran; Shasidaran Shasidaran; D Sharad Gedam (International Journal of Medical Research and Review, 2017)
Trauma is a major cause of mortality worldwide. Majority of trauma deaths occurs within 24 hours of injury. Survival depends on timely resuscitation. Initial evaluation uses primary survey involving Airway maintenance, Breathing, Circulation, Disability and Exposure. In secondary survey, thorough head to toe examination is done. Initial resuscitation begins with 2 intravenous access and restricted volume replacement strategy.Controlling active bleeding, treating coagulopathy and transfusion of appropriate fluids is mandatory. Hypothermia should be treated with passive/ active peripheral warming and core warming. Ventilation strategy should be focussed to avoid hypoxaemia, hyperventilation and hypocapnia. Colloids (albumin, hydroxyethyl starches, dextrans, gelatins) and crystalloids (normal saline, ringer’s lactate) are both used in resuscitation. For major blood volume loss, blood transfusion is recommended to maintain tissue oxygenation. Damage Control Resuscitation is the strategy for hemorrhagic shock management which requires large-volumes of blood product transfusion.Vasopressors maintain target arterial pressure in presence of myocardial dysfunction. For patients with expected massive haemorrhage, Plasma or Fibrinogen concentrate and RBC may be used.Head trauma severity is age specific. Sedation, analgesia and fluids should be started. Secondary injury from hypoxia, hypotension, hyperthermia or raised intracranial pressure should be avoided. After structured approach of airway, breathing, circulation and disability, definitive treatment of primary intracranial injury should be done. CT scan is done for moderate/ severe head trauma or if signs of basal skull fracture. Management of trauma patients is challenging and requires a multidisciplinary approach.